Impacts of climate change on inundation and salinity intrusion of Cuu Long delta - Tuyen, Hoang Minh (VNU Journal of Science: Earth and Environmental Sciences; Vol 27 No 2, 2011)
Abstract. Base on the results of the flow simulated by Mekong River Commission (MRC), combined with Sea Level Rise (SLR) and salinity scenarios by IMHEN, the paper presents impacts of CC on flooding and salinity intrusion in Cuu Long Delta. By 2050, the maximal flooded area which is more than 0.5 m depth can be up to 68.3% of the entire area of Cuu Long Delta. The maximum distance of salinity intrusion increases in the main rivers can reach by 10 km by the middle of the 21 st century. The area affected by salinity intrusion at >4 ‰ occupies 41% area of all Cuu Long Delta and by salinity >1 ‰ is 59% of natural area. Keywords: Inundation, salinity intrusion, Cuu Long, climate change.